Lumbar Canal Stenosis: A Prospective Clinicoradiologic Analysis - Jain, Nikhil; Acharya, Shankar; Adsul, Nitin Maruti; Haritwal, Mukesh Kumar; Kumar, Manoj; Chahal, Rupinder Singh; Kalra, Kashmiri Lal (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background Although spinal canal narrowing is thought to be the defining feature for the clinical diagnosis of lumbar canal stenosis, the degree of spinal canal stenosis necessary to elicit neurologic symptoms is not clear. Several studies have been performed to detect an association between a narrow spinal canal and clinical symptoms. Through our prospective study, we compared the radiologic criteria with the clinical criteria using the Oswestry Disability Index (ODI) and assessed how they correlate.Materials and Methods We used the qualitative grading (morphological classification system on magnetic resonance imaging [MRI]) system, dural sac cross-sectional area (DSCA), and sedimentation sign on MRI images and compared them with the Self-Paced Walking Ability (Self-Paced Walking Test) and ODI of the patients in the study. The systems were applied to 85 patients divided into three groups: group A: 43 patients with neurogenic claudication and able to walk < 30 minutes; group B: 11 patients with neurogenic claudication and able to walk > 30 minutes; and group C: 31 patients with simple back pain and no signs of neurologic claudication.Results The mean ODI was 21.19 in group C, 46.50 in group B, and 61.95 in group A. The difference was statistically significant. The mean DSCA was 164.42 mm2 in group C, 49.94 mm2 in group B, and 35.07 mm2 in group A. The difference was statistically significant. The sedimentation sign was negative in 96.8% patients in group C, 54.5% patients in group B, and 32.6% patients in group A. The difference was statistically significant. Group C had 9.3% patients in morphology grade A3, 51.6% in grade A2, and 38.7% patients in grade A1. Group B had 63.6% patients in grade C, 18.2% patients in grade B, 9.1% in grade A4, and 9.1% in grade A3. Group A had 18.6% patients in grade D, 39.5% in grade C, 27.9% in grade B, 11.6% in grade A4, and 2.3% in grade A3. The mean DSCA of group C was significantly different from group A and group B, but the difference of the mean DSCA between group A and group B was not statistically significant. The relationship of ODI to DSCA, ODI to sedimentation sign, and ODI to morphological grading for group C and group A was not statistically significant. The relationship of morphological grading to DSCA was statistically significant for all three groups.Conclusion DSCA, morphological grading, and sedimentation sign are good to excellent radiologic indicators differentiating patients with simple back pain from those with lumbar spinal stenosis. Clinically, ODI is an excellent indicator of the severity of stenosis. But ODI statistically has no significant correlation to any of these radiologic parameters.
Keywords: lumbar; canal; stenosis; clinicoradiologic; analysis